Inclusion in Industry : Advancing Equality for Disabled Workers in Manufacturing in Indonesia - Hizwati Dalilati Hazhiyah; Indra Kertati (Universitas 17 Agustus 1945 Semarang, 2025)
The manufacturing industry plays a pivotal role in promoting workplace equality for employees with disabilities. This paper explores the historical context, current trends, and challenges faced by disabled workers in the manufacturing sector. Through a comprehensive literature review and empirical research, including surveys, interviews, and case studies, the study identifies significant barriers to inclusion, such as physical inaccessibility, attitudinal prejudices, and inadequate policies. It also highlights best practices and policies that manufacturing companies can adopt to foster an inclusive environment. These include inclusive hiring practices, workplace accommodations, and training programs to raise awareness and sensitivity among employees. The research showcases successful implementations of inclusive practices in various manufacturing companies, emphasizing the economic and social benefits of such initiatives. Increased productivity, innovation, and improved workplace morale are among the noted advantages. The paper concludes with recommendations for enhancing inclusion in the manufacturing industry and suggests future research directions to continue advancing equality for disabled workers. By addressing these challenges and adopting best practices, the manufacturing industry can set a benchmark for other sectors, demonstrating that inclusivity is not only a moral imperative but also a driver of business success.